Tracking the evolution of the SARS-CoV-2 Delta variant of concern: analysis of genetic diversity and selection across the whole viral genome - Li, Katherine; Melnychuk, Stephanie; Sandstrom, Paul; Ji, Hezhao (Frontiers in Microbiology, 2023)
Background: Since 2019, SARS-CoV-2 has diversified extensively, producing five highly virulent lineages designated as variants of concern (VOCs). The Delta VOC emerged in India with increased transmission, immune evasion, and mortality, causing a massive global case surge in 2021. This study aims to understand how the Delta VOC evolved by characterizing mutation patterns in the viral population before and after its emergence. Furthermore, we aim to identify the influence of positive and negative selection on VOC evolution and understand the prevalence of different mutation types in the viral genome. Methods: Three groups of whole viral genomes were retrieved from GISAID, sourced from India with collection periods as follows. Group A: during the initial appearance of SARS-CoV-2; Group B: just prior to Delta’s emergence; Group C: after Delta’s establishment in India. Mutations in >1% of each group were identified with BioEdit to reveal differences in mutation quantity and type. Sites under positive or negative selection were identified with FUBAR. Results were compared to determine how mutations correspond with selective pressures and how viral mutation profiles changed to reflect genetic diversity before and after VOC emergence. Results: The quantity of mutations increased progressively from Group A-C, with Group C reporting a 2.2- and 1.9-fold increase from Group A and B, respectively. Among all the observed mutations, Group C had the highest percentage of deletions (22.7%; versus 4.2% and 2.6% in Groups A and B, respectively), and the most mutations altering the final amino acid code, such as non-synonymous substitutions and deletions. Conversely, Group B had the most synonymous substitutions that are effectively silent. The number of sites experiencing positive selection increased from Groups A-C, but Group B had 2.4- and 2.6- times more sites under negative selection compared to Group A and C, respectively. Conclusion: Our findings demonstrated that viral genetic diversity continuously increase during and after the emergence of the Delta VOC. Despite this, Group B reports heightened negative selection which potentially preserves important gene regions during evolution. Group C contains an unprecedented quantity of mutations and positively selected sites, providing strong evidence of active viral adaptation in the population.